(untitled) (Fiep Bulletin - online, 2014)
It’s widely known that soccer represents a sports modality that dominates both amateur and professional sports in Brazil and makes children show less interest in other modalities. The current study aims at providing the opportunity of learning the fundamental technical gestures for the practice of handball through the HandTutor software. To do so, theoretical underpinnings were used from the existent bibliography as well as the researcher’s previous theoretical knowledge on the subject. The final result of this study allows us to come to the conclusion that the learning of handball is, contrary to popular belief, as simple as other sports modalities which in turn is threatened due to the lack of preparation of the professionals who work in the area as well as the lack of knowledge of such modality. Through this software, we hope to show what handball is and also to make this sports practice more popular among the others.